Sorption Behaviour of Trichlorobenzenes and Polycyclic Aromatic Hydrocarbons in the Absence or Presence of Carbon Nanotubes in the Aquatic Environment - Trickovic Jelena (WATER AIR AND SOIL POLLUTION, 2016)
This work investigates the sorption behaviour of six hydrophobic organic compounds (HOCs) from the trichlorobenzenes (TCBs) and polycyclic aromatic hydrocarbons (PAHs) on Danube sediment using batch and column experiments, either in the presence or absence of carbon nanotubes (CNTs). For all HOCs investigated, nonlinear isotherms were obtained. Based on logKoc, it can be concluded that the Danube sediment has a higher sorption affinity for PAHs than TCBs. A positive correlation between HOC molecular hydrophobicity and sorption affinity was obtained, meaning that hydrophobic interactions play a significant role. There was a negative correlation between molecular hydrophobicity and the percentage of eluted HOCs, indicating that more hydrophobic molecules show less mobility in the sediment column. In the presence of CNTs in the sediment column, HOC concentrations in the column eluate decreased by factors of 2–3. Metal oxides and hydroxides on the surface of the sediment under the given experimental conditions had positively charged centres that caused the deposition of CNTs, leading to simultaneous sorption of organic compounds on both sediment organic matter (SOM) and CNTs. The increased retention of HOCs in the presence of CNTs on the sediment column reduces their mobility, which might also suggest that CNTs may be used for remediation of contaminated soils and sediments.